Influence of solid and liquid hydrophobic compounds on characteristics of water located in an adsorption layer of a hydrophilic component of the system - V. V. Turov; V. M. Gun'ko; T. V. Krupska; M. T. Kartel (Хімія, фізика та технологія поверхні)
The aim of this study was to analyze the temperature and interfacial behavior of water bound to A-300,  A-300/AM1 and Al2O3/AM1 initial and mechanically treated and located in air, chloroform alone or with addition of trifluoroacetic acid (TFAA) using low-temperature 1H NMR spectroscopy and cryoporometry. Properties of unmodified (A-300) and modified (AM1) (1 : 1) nanosilicas, as well as nanoalumina, were studied in air or chloroform alone or with addition of TFAA using 1H NMR spectra recorded at different temperatures and related cryoporometry. In nontreated composite, water interaction with nanosilica (hydration degree h = 1.125 g/g) increases and free surface energy gS grows by five times due to water reorganization into nanoclusters and similar clusters are absent in cA-300 due to several factors. After the mechanical treatment (bulk density increases to rb » 1.2 g/cm3), water interaction energy with nanosilicas becomes smaller (by three times for CDCl3 and ten times for air medium) than that for nontreated composite. The effects of CDCl3 are much stronger for water in nontreated system than those in compacted composite. This is due to reorganization of water affected both by changes in the confined space effects and the influence of hydrophobic chloroform, which can displace water into small voids (inaccessible for larger chloroform molecules) or larger voids to reduce the contact area of both liquids. Thus, it has been shown that the observed influence of the hydrophobic components in complex hydrophobic/hydrophilic systems on enhancement of water binding to hydrophilic components is the general phenomenon caused by both the confined space effects and features of interactions of water with various hydrophobic structures such as the surface functionalities of hydrophobic silica and hydrophobic liquid (chloroform) or proton-donor components (TFAA).